FACTORS FOR ACTIVATING THE EXPORT POTENTIAL OF UKRAINE’S AGRARIAN BUSINESS - ZHYHYLII, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In modern conditions, the agricultural sector of Ukraine is one of the key sources of foreign exchange earnings and a factor in stabilizing the national economy. The purpose of the study is to substantiate the list and features of the influence of factors activating the export potential of Ukraine’s agrarian business in the face of modern challenges. Based on statistical data, the export potential of agricultural enterprises in Ukraine was analyzed by comparing the dynamics of the share of added value of agriculture, forestry, and fisheries in GDP and exports of goods and services for the period 2010-2024. The study showed that the share of the agro-industrial complex in the country’s GDP over the past decade has remained significant, and agricultural products have consistently formed a significant part of total exports. It was found that the export potential of the agrarian business is far from being fully realized, which is due to both internal restrictions and adverse external conditions. Military actions, blocking of logistics routes, changes in market conditions, and instability of the legislative field create additional risks for export activities. At the same time, the country retains a unique competitive advantage, namely fertile soils, developed production of raw materials, and the availability of technological potential. The list of main types of factors influencing the export potential of Ukraine’s agrarian business is also summarized, considering the direction and nature of such influence at the current stage of development of the business environment. The development of mechanisms for activating exports will contribute to economic growth, employment in rural areas, and the formation of a positive image of Ukraine in the world market. Modern challenges necessitate a reevaluation of export policy in the agricultural sector, focusing on the efficient use of resources, integration into global value chains, and enhancing the export capacity of agrarian businesses.